1978
DOI: 10.1113/jphysiol.1978.sp012170
|View full text |Cite
|
Sign up to set email alerts
|

Human muscle nerve sympathetic activity at rest. Relationship to blood pressure and age

Abstract: SUMMARY1. Recordings of multi-unit sympathetic activity were made from median or peroneal muscle nerve fascicles in thirty-three healthy subjects, resting in recumbent position. Simultaneous recordings of intra-arterial blood pressure were made in seventeen subjects. The neural activity, quantified by counting the number of pulse synchronous sympathetic bursts in the mean voltage neurogram (burst incidence), was plotted against the arterial blood pressure level and the age of the subjects. The effects of spont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
509
5
10

Year Published

1983
1983
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 552 publications
(546 citation statements)
references
References 27 publications
22
509
5
10
Order By: Relevance
“…To this end, the present investigation examined sympathetic nervous system activation in healthy young and older adults using a standardized whole body skin surface cooling protocol via water-perfused suit (3,30,51,55). Consistent with a wide body of literature examining MSNA at rest in older adults at thermoneutrality (27,39,53), older adults in the present study exhibited increases in basal muscle sympathetic outflow. Furthermore, whole body cold stress elicited pronounced increases in MSNA burst frequency and strength in older, but not young, adults.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…To this end, the present investigation examined sympathetic nervous system activation in healthy young and older adults using a standardized whole body skin surface cooling protocol via water-perfused suit (3,30,51,55). Consistent with a wide body of literature examining MSNA at rest in older adults at thermoneutrality (27,39,53), older adults in the present study exhibited increases in basal muscle sympathetic outflow. Furthermore, whole body cold stress elicited pronounced increases in MSNA burst frequency and strength in older, but not young, adults.…”
Section: Discussionsupporting
confidence: 65%
“…MSNA and plasma norepinephrine concentrations are elevated with advancing age (15,24,27,39,53); therefore, impairments in norepinephrine-mediated vasoconstriction have generally been attributed to sustained agonist-mediated desensitization in ␣-adrenergic receptor responsiveness (24). Conversely, the age-related increase in MSNA during cooling may be a compensatory response as a result of age-associated reductions in ␣-adrenergic receptor responsiveness.…”
Section: Discussionmentioning
confidence: 98%
“…However, greater arterial blood pressure levels in the EHT groups were associated with a greater rather than smaller sympathetic nerve activity than in the NC groups as has been commonly reported previously. [4][5][6][7][8]14 Also, there were no significant differences in arterial blood pressure levels between women and men within the EHT or the NC groups, although as has previously been reported elsewhere, 6,35,36 we found no significant correlation between sympathetic nerve activity and arterial blood pressure level in individual subjects. Indeed, the differences in sympathetic nerve activity between women and men within the EHT or the NC groups were greater than the variability attending repeated measurements of this activity.…”
Section: For Hypertensive Women (F-eht) and Men (M-eht) Normotensivesupporting
confidence: 66%
“…Several studies in heart failure patients show that sympathetic hyperactivity is triggered by lower BRS 33, 34, 35. We observed that spontaneous BRS is decreased either BRS+ or BRS− in patients with RCM.…”
Section: Discussionsupporting
confidence: 49%